Leadership Perception during COVID-19 Pandemic: The Critical Criticism on Surgical Leadership - Adeel Abbas Dhahri; Ubaid Ur Rehman; Syeda Shahana Ali; Muhammad Hussnain Iqbal; Alexandra Lupu; Mehvish Adeel Dhahri; Jonathan Refson (Ital Publication, 2021)
Coronavirus disease 2019 (COVID-19) has altered the expectations of team leaders by team members while they seek clear and efficient decisions. We aim to assess the perception of leadership by the surgical team members and their perception of the most important quality of leadership. We conducted an online national cross-sectional survey among the surgical doctors working in the National Health Service United Kingdom, between 15th July 2020 till 31st August 2020. The questionnaire, based on rating scale items, focused on effects of changes in work-pattern, support and communication at workplace, the status of leadership and understanding of different leadership attributes. Out of two hundred and thirteen participants, majority of respondents were middle-grade registrars (n= 92, 43.7%). Most of the doctors (147,81.7%) were never re-deployed to the high-risk areas. 85(39.9 %) expressed that COVID-19 brought distress affecting their morale. 106(49.8%) thought that arrangement of Personal Protective Equipment (PPE) was the responsibility of the Head of Department. The majority, of those who fell ill, felt adequately supported by their seniors. Most participants identified departmental leadership as satisfactory (n=126, 59.2%). There was a mixed response to the importance of leadership attributes defined by the Faculty of Medical Leadership and Management. Stress at the workplace with reduced morale, during a crisis like COVID-19 pandemic, can significantly compromise leadership perception among team members. Understanding of basics of leadership by the team members can improve departmental efficiency and as a result improve patient care.   Doi: 10.28991/SciMedJ-2021-0303-6 Full Text: PDF